2015
DOI: 10.1520/gtj20140047
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Study on the Shear Behavior of Mixtures of Coal Wash and Steel Furnace Slag as Potential Structural Fill

Abstract: The accumulation of industrial waste materials (e.g., coal wash and steel furnace slag) has become a critical environmental problem in Australia in recent years. The possible re-use of these types of materials as structural fill for transport embankments and land reclamation is one of the preferred options from a waste management perspective. Consequently, an experimental testing program was undertaken using the triaxial apparatus to evaluate the shear behavior of compacted mixtures of coal wash (CW) and steel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…1. Following a previous study by Tasalloti et al (2015), to achieve the target particle size distribution (PSD), the waste materials were sieved and separated into different particle sizes, and the exact mass corresponding to a given size range was weighed and mixed thoroughly to obtain a uniform blend. All the specimens were prepared at the optimum moisture content and compacted to achieve an initial dry unit weight equivalent to 95% of their γ ୢ୫ୟ୶ (Table 3) to simulate typical field conditions of subballast.…”
Section: Specimen Preparation and Test Proceduresmentioning
confidence: 99%
“…1. Following a previous study by Tasalloti et al (2015), to achieve the target particle size distribution (PSD), the waste materials were sieved and separated into different particle sizes, and the exact mass corresponding to a given size range was weighed and mixed thoroughly to obtain a uniform blend. All the specimens were prepared at the optimum moisture content and compacted to achieve an initial dry unit weight equivalent to 95% of their γ ୢ୫ୟ୶ (Table 3) to simulate typical field conditions of subballast.…”
Section: Specimen Preparation and Test Proceduresmentioning
confidence: 99%
“…The coalwash has a plasticity index of 10.7%, a liquid limit of 27.7% and a specific gravity of 2.23; thus, it can be classified as clayey sand or SC (Unified Soil Classification System). The properties of coalwash are elaborated in detail by Rujikiatkamjorn et al (2013), Chiaro et al (2014) and Tasalloti et al (2015). The curves representing the coalwash tailings (Indraratna et al, 1994) and the arbitrary boundary of maximum permissible breakage are also shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…RC usually mixed with sand, clay, fine-grained soil, fine recycled glass, crushed rock or asphalt to serve as lightweight landfill, highway embankments, flexible or permeable pavements, as well as for applications in seismic isolation (Fu et al 2017;Ajmera et al 2017;Lee et al 1999;Li et al 2016;Tsang et al 2012;Sheikh et al 2013;Disfani et al 2017;Mohammadinia et al 2018;Yaghoubi et al 2018). It is reported that the blends of SFS and CW can reduce the swelling of SFS and the particle breakage of CW, and a SFS+CW mixture with an appropriate ratio of SFS:CW has been successfully applied in Wollongong port reclamation (Chiaro et al 2013;Tasalloti et al 2015). To extend the application of SFS+CW mixtures into dynamic loading projects (e.g.…”
Section: Introductionmentioning
confidence: 99%